Single-phase Multilevel Inverter with Simpler Basic Unit Cells for Photovoltaic Power Generation - M. S. Chye; J. A. Soo; Y. C. Tan; M. Aizuddin; S. Lee; M. Faddle; S. L. Ong; T. Sutikno; J. H. Leong (Institute of Advanced Engineering and Science, 2016)
This paper presents a single-phase multilevel inverter (MLI) with simpler basic unit cells. The proposed MLI is able to operate in two modes, i.e. charge mode to charge the batteries, and inverter mode to supply AC power to load, and therefore, it is inherently suitable for photovoltaic (PV) power generation applications. The proposed MLI requires lower number of power MOSFETs and gate driver units, which will translate into higher cost saving and better system reliability. The power MOSFETs in the basic unit cells and H-bridge module are switched at near fundamental frequency, i.e. 100 Hz and 50 Hz, respectively, resulting in lower switching losses. For low total harmonic distortion (THD) operation, a deep scanning method is employed to calculate the switching angles of the MLI. The lowest THD obtained is 8.91% at modulation index of 0.82. The performance of the proposed MLI (9-level) has been simulated and evaluated experimentally. The simulation and experimental results are in good agreement and this confirms that the proposed MLI is able to produce an AC output voltage with low THD.